COVID-19 IN PAKISTAN: WHERE DO WE STAND AND WHAT IS THE WAY FORWARD? COVID-19 in Pakistan - Basharat, Sarah; Shaikh, Babar Tasneem; Abdullah, Muhammad Ahmed (Journal of Ayub Medical College Abbottabad, 2021)
At the outset of year 2020, COVID-19 emerged as a new public health threat and the world resorted to a diverse range of combating plots including lock down downs, social distancing, advocating precautions like wearing masks, using sanitizers etc. Pakistan followed the same pathway despite the fact that the virus resulted in less severe morbidity and mortality as compared to the rest of the world. Nevertheless, the fear and panic it created due owing to virulence and subsequent outcomes of corona illness was of alarming magnitude. Pakistan went for smarter, conservative and prudent plans and kept the balance between saving lives and livelihoods. Health system showed its inherent weaknesses and it was soon realized that a multi-sectoral response would be needed to address the catastrophe. A large majority is inclined to call it a '˜new normal' and is persuading to go on with life; for sure, by adopting a health system thinking.